2017
DOI: 10.1177/1742271x17733145
|View full text |Cite
|
Sign up to set email alerts
|

Automated quality control of ultrasound based on in-air reverberation patterns

Abstract: Ultrasound image degradation originates primarily from transducer defects and potentially undermines reliable image interpretation. Systematic quantitative quality control is often neglected due to the limited resources available for this task. We propose a quantitative quality control based on in-air reverberation images. These images serve as an initial indication of image degradation. They are easily generated for any (curvi-)linear transducer independent of the level of expertise of the operator. Automated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…These artifacts were, however, not substantial to change the U skew values. 4 The defective transducers showed values of −1.81%, −1.37% and −2.15% respectively. As expected, these were large negative values, that indicated that the transducers were defective.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…These artifacts were, however, not substantial to change the U skew values. 4 The defective transducers showed values of −1.81%, −1.37% and −2.15% respectively. As expected, these were large negative values, that indicated that the transducers were defective.…”
Section: Resultsmentioning
confidence: 96%
“…26,27 Since ultrasound image quality, either good or bad, it is primarily due to transducer defects, which compromises image interpretation’s reliability. 4,19 -21 However, as noted in a study by Mårtensson et al, 2 the frequency of quality control should be determined by operators based on equipment use, as the transducer’s function is not yet fully understood. Therefore, the ultrasound equipment manufacturer provides a list of recommended quality assurance procedures in the operator’s manual for each machine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations